Perceptions of managers about gender based violence in the university (Research, Society and Development, 2022)
Aims: To describe and analyzed the perceptions of university managers about the violence in the university. Methodology: A questionnaire, approaching the knowledge, opinion, and experience on gender based violence (GBV) and the procedures to confront it, was administered to 101 university managers. The analysis was carried out using descriptive statistics and the search for an association between the independents and dependents variables using the Pearson Chi-Square and the Fisher Exact Test. Results and conclusion: The knowledge about GBV was considered low for 27.7% of participants, medium for 44.5%, and high for 27,7%. The knowledge about the procedures to be carried out to confront GBV  in the university context was classified as low for 34.0%, medium for 33.0%, and high for 33.0%. Regarding the opinion they have about the GBV at the university, 50.5% are a little reactive and 49.5% are very reactive towards it. An association between higher knowledge about GBV at the university and having witnessed discrimination was found, as well as being more reactive and having received complaints and witnessed more cases of violence.